Realidade Virtual como Abordagem Terapêutica Não Farmacológica para a Depressão na Demência: Uma Revisão Sistemática - Joana Jardim Freitas Soares (2022)
Objectives: Depression is one of the most frequent behavioral and psychological symptoms of dementia (BPSDs) and, when untreated, has been associated with a range of negative outcomes. Virtual reality (VR) has been gaining popularity as a non-pharmacological approach to BPSDs. However, the efficacy of VR in dementia-related depression is still uncertain. This review aims to evaluate the effect of VR interventions in the reduction of depression or depressive symptoms in people with dementia (PwD). Methods: A systematic review was conducted following PRISMA 2020 guidelines and the study protocol was registered in PROSPERO. PubMed, Scopus, and Web of Science databases were searched from inception to March 2022 for intervention studies evaluating the effect of VR in depression. For each eligible study, risk of bias was assessed with Cochrane "Risk of Bias" tool (RoB 2.0) and Risk of Bias In Non-randomized Studies of Interventions tool (ROBINS-I). A narrative synthesis was undertaken. Results: Of 617 records identified, six studies fully met the eligibility criteria. These comprise 300 PwD. Two studies were deemed to have "some concerns" risk of bias, and four "high"/"critical" risk. Three studies reported no statistically significant effects of VR compared to the control group or to baseline patient data, and three reported significant positive effects. Conclusions: So far, only weak evidence that VR interventions may benefit depression in PwD is provided. Notwithstanding this, VR holds promise as no increase in depressive symptoms has been reported, so future research should address the methodological limitations and narrow scope of the existing evidence.